American experience [videorecording (DVD)]. War of the worlds - Platt, Oliver (PBS, 2013)
What began as a broadcast performance of H.G. Wells' fantasy, The War of the Worlds, turned into one of the biggest mass hysteria events in U.S. history. American Experience examines the elements that together created this frenzy, including our longtime fascination with life on Mars; the emergence of radio as a powerful new medium; and the creative wunderkind Orson Welles, the twenty-three-year-old director of the drama and mischief-maker supreme.